Hubungan Kondisi Fisik Rumah Dan Faktor Manusia DenganKejadian ISPA Pada Balita Di Wilayah Kerja Puskesmas Garuda Kelurahan Tangkerang Pekanbaru Tahun 2019 - Elmia kursani; Beny Yulianto; Widya Safitri Ramadhani (Viva Medika, 2019)
ISPA is an acute respiratory disease with a variety of symptoms such as cough, runny nose, fever and breath sounds which last for 14 days. ISPA death in infants and toddlers is 20% -30% caused by ISPA. The purpose of this study was to determine the relationship between the physical condition of the house and human factors with the incidence of ISPA in infants in the Work Area of ​​the Garuda Public Health Center, Tangkerang Tengah Village, Pekanbaru in 2019. The method of this research is quantitative with Cross Sectional research design. The population in the study were all mothers who have toddlers in the Working Area of the Puskesmas Garuda Kelurahan Tangkerang Tengah Pekanbaru. The research sample was 100 respondents with the Stratified Random Sampling sampling technique. The analysis used was univariate and bivariate with the chi square test, the measuring instruments used were questionnaires, observation sheets, lighting gauges, tape meters and data processing using computers. The results showed that there was a significant relationship between ventilation value = 0.006 (alpha <0.05), occupancy density value of 0.001 (alpha <0.05), lighting value 0.029(alpha<0.05), smoking habit value 0.002 (alpha < 0.05), the temperature of Pvalue is 0.226 (alpha<0.05), maternal knowledge is 0.024 (alpha <0.05) with the incidence of ISPA. It is suggested that the health center can work with the community to conduct counseling about healthy homes and about ISPA so that it can increase the knowledge of the community, especially mothers who have toddlers